EVALUASI KONDISI STRUKTUR BETON BERTULANG PADA BANGUNAN EKSISTING MENGGUNAKAN METODE NDT DAN PENYUSUNAN STRATEGI PEMELIHARAAN BERBASIS KLASIFIKASI MUTU - Reni Suryanita; Vinka Lyona; Randhi Saily; Intan Monica MG; Harnedi Maizir; Raihan Arditama Harnedi (Jurnal Infrastruktur, 2025)
The assessment of reinforced concrete (RC) building structures is a critical step in ensuring the sustainability and functional reliability of existing facilities. This study aims to evaluate the quality of concrete using Non-Destructive Testing (NDT) methods—namely Rebar Locator, Rebound Hammer (RH), and Ultrasonic Pulse Velocity (UPV)—and to formulate maintenance strategies based on concrete quality classification. Testing was conducted on six column locations of a three-story office building, with measured compressive strength values ranging from 36.3 MPa to 48.9 MPa and ultrasonic pulse velocities ranging from 2.57 m/s to 4.75 m/s. The test results were interpreted to determine the condition levels of the concrete, which subsequently served as the basis for recommending appropriate maintenance actions. The findings revealed that structural elements at Level 1 were classified as Excellent, whereas Levels 2 and 3 exhibited conditions ranging from Good to Doubtful. Maintenance strategies were formulated accordingly, encompassing routine maintenance, localized repair, and structural strengthening in critical areas. This NDT-based approach enhances the accuracy of condition-based maintenance planning and contributes to both the sustainability and safety of reinforced concrete building structures.